Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1371/journal.pone.0026971
|View full text |Cite
|
Sign up to set email alerts
|

Serum MicroRNA-21 as Marker for Necroinflammation in Hepatitis C Patients with and without Hepatocellular Carcinoma

Abstract: BackgroundMicroRNA-21 (miR-21) is up-regulated in tumor tissue of patients with malignant diseases, including hepatocellular carcinoma (HCC). Elevated concentrations of miR-21 have also been found in sera or plasma from patients with malignancies, rendering it an interesting candidate as serum/plasma marker for malignancies. Here we correlated serum miR-21 levels with clinical parameters in patients with different stages of chronic hepatitis C virus infection (CHC) and CHC-associated HCC.Methodology/Principal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
2
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 33 publications
8
84
2
5
Order By: Relevance
“…Our miRNA-21 results are not matching with many other studies that report an up-regulation of miRNA-21 in many cancers including HCC [14]- [19]. Bihrer et al [20] demonstrated that the level of miRNA-21 in sera from patients with chronic hepatitis C associated HCC was elevated compared to healthy controls. But they also detected increased levels of miRNA-21 in sera from patients with chronic hepatitis C without HCC, suggesting that this elevation of serum miRNA-21 levels appears to be mainly associated with chronic hepatitis rather than HCC.…”
Section: Discussioncontrasting
confidence: 99%
“…Our miRNA-21 results are not matching with many other studies that report an up-regulation of miRNA-21 in many cancers including HCC [14]- [19]. Bihrer et al [20] demonstrated that the level of miRNA-21 in sera from patients with chronic hepatitis C associated HCC was elevated compared to healthy controls. But they also detected increased levels of miRNA-21 in sera from patients with chronic hepatitis C without HCC, suggesting that this elevation of serum miRNA-21 levels appears to be mainly associated with chronic hepatitis rather than HCC.…”
Section: Discussioncontrasting
confidence: 99%
“…This miRNA is the first to be studied as a therapeutic tool and other two studies (Connolly et al, 2008;Zhu et al, 2011) have shown that the transfection of tumor cells with antisense oligonucleotides specific for mir-21 leads to a reduction of the cell growth and survival. Likewise studies by Xu et al (2011a), Bihrer et al (2011), Marquez et al (2010 have shown that serum levels of miR-21 are increased with a progressive course from chronic hepatitis to cirrhosis and hepatocellular carcinoma. Multivariate analyses demonstrate that the only parameters to be associated with this miRNA are histological necroinflammation and viral load.…”
Section: Mir-21mentioning
confidence: 89%
“…Different serum-miRNAs were found to correlate with liver inflammation and fibrosis indirectly caused by the virus. 46,47 Various studies reported on miRNA expression in hepatocellular carcinoma tissue of HCV-positive patients, but again these findings are likely not exclusively caused by HCV infection but rather by the tumor itself or again by HCV-induced liver damage. 7,48,49 The diminished expression of miR-26b, as seen in the HCV-positive lymphoma group, has been linked to a malignant tumor phenotype in hepatocellular carcinoma 50 and lung carcinoma 51 as well as in cell culture models of colon cancer and diffuse large B-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%